1983
DOI: 10.1111/j.1365-3180.1983.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Setaria chevalieri caryopses

Abstract: Summary Germination studies were made on Setaria chevalieri caryopses (seeds). The seeds imbibed readily upon moist incubation. An after‐ripening period which followed a cyclic patlern was necessary for maximum germination. Freshly harvested seed germinated in the presence of light, but only very sporadically in the dark. The germination of dark incubated seed was improved if the seeds were subsequently exposed to light. This photodormancy became less pronounced with dry storage. Treatment with red light incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Cyclic changes in seed dormancy occur in many species which exhibit seasonal patterns of emergence (Baskin & Baskin, 1978Froud-Williams, Drennan & Chancellor, 1984) but such changes have not been reported during dry-storage (Karssen, 1980/81a). However, Erasmus & van Staden (1983) have observed that caryopses of Setaria chevalieri germinated less after 10 weeks of dry-storage than either immediately after collection or after 24 weeks of dry-storage. Nonetheless, this represents a period of after-ripening to break post-harvest dormancy rather than cyclic changes per se.…”
Section: Discussionmentioning
confidence: 92%
“…Cyclic changes in seed dormancy occur in many species which exhibit seasonal patterns of emergence (Baskin & Baskin, 1978Froud-Williams, Drennan & Chancellor, 1984) but such changes have not been reported during dry-storage (Karssen, 1980/81a). However, Erasmus & van Staden (1983) have observed that caryopses of Setaria chevalieri germinated less after 10 weeks of dry-storage than either immediately after collection or after 24 weeks of dry-storage. Nonetheless, this represents a period of after-ripening to break post-harvest dormancy rather than cyclic changes per se.…”
Section: Discussionmentioning
confidence: 92%